MOLECULAR DYNAMICS COMPUTER SIMULATIONS OF MULTIDRUG RND EFFLUX PUMPS - Paolo Ruggerone; Attilio V. Vargiu; Francesca Collu; Nadine Fischer; Christian Kandt (Computational and Structural Biotechnology Journal, 2013)
Over-expression of multidrug efflux pumps of the Resistance Nodulation Division (RND) protein super family counts among the main causes for microbial resistance against pharmaceuticals. Understanding the molecular basis of this process is one of the major challenges of modern biomedical research, involving a broad range of experimental and computational techniques. Here we review the current state of RND transporter investigation employing molecular dynamics simulations providing conformational samples of transporter components to obtain insights into the functional mechanism underlying efflux pump-mediated antibiotics resistance in Escherichia coli and Pseudomonas aeruginosa.